Anti-Corruption Campaigns and Nigeria’s Development: An Appraisal of Media in Nigeria - Kamaldeen Arikewuyo Ahmed; Saudat Sallah Abdulbaqi, (Journal of Human Development and Communication (JoHDeC), 2025)
Challenges in Nigerian development is partly linked to corruption. Nigeria suffers significantly from the problem of corruption which begets malnutrition, illiteracy, poverty, unemployment, hunger and infrastructure decay. Due to the failures of numerous development strategies in Nigeria, this paper provides an overview of mass media efforts in fighting corruption to discern developments and proceed with the validation of social responsibility and development media theory in campaigning against the said corruption. Using secondary data of Transparency International from (2000-2018) on the World Corruption Perception Index and Ranking, the study revealed that the media have been very relevant in curbing corruption and entrenching development through its watchdog role and mass enlightening in the provision of information that facilitates job creation, economy improvement, enhanced security and re-orientation of the masses. The study also revealed that the level of bribery, looting of treasury, abuse of power and secret dealings are perceived to be rapidly reducing in Nigeria. Further, the study showed that Nigeria moved from 148th to 144th position out of 180 countries in the 2018 (CPI) report of corrupt countries. Hence, this paper proposes critical media independence, vibrant and active judicial system coupled with exemplary leadership for more feasible development schemes in Nigeria.